2023
DOI: 10.1159/000529908
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socio-Environmental, Individual, and Biological Factors on Oral Health-Related Quality of Life among Preschool Children: A Cohort Study with 3-Year Follow-Up

Abstract: This study assessed impact of socio-environmental, individual and biologic factors on the worsening and severe worsening of oral health-related quality of life (OHRQoL) among preschoolers and their families. A cohort study was conducted in Diamantina, Brazil, with 151 children between one and three years of age and their mothers, who were evaluated at baseline (2014) and re-evaluated after three years (2017). The children were clinically examined to assess the presence of dental caries, malocclusion, dental tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…The mean score obtained by the responses of parents/guardians on the SOC 13 scale was 46.27, a mean similar to the studies of Bonanato et al 17 14 , which obtained 47.50 and 47.2 points, respectively. The total score in the study ranged from 22 to 62 points, similar to the study of Bonanato et al 17 A significant percentage (84.1%) of children participating in this study used the dental service at least once in their lives and about 16% had never been to the dentist, findings that are relatively lower (18.9%) than those reported by da Silva et al 22 (2011) and those presented in the last national survey on oral health (18.1%) 23 , which may express the increased access to and use of dental services by children, as also identified in a previous study 24 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The mean score obtained by the responses of parents/guardians on the SOC 13 scale was 46.27, a mean similar to the studies of Bonanato et al 17 14 , which obtained 47.50 and 47.2 points, respectively. The total score in the study ranged from 22 to 62 points, similar to the study of Bonanato et al 17 A significant percentage (84.1%) of children participating in this study used the dental service at least once in their lives and about 16% had never been to the dentist, findings that are relatively lower (18.9%) than those reported by da Silva et al 22 (2011) and those presented in the last national survey on oral health (18.1%) 23 , which may express the increased access to and use of dental services by children, as also identified in a previous study 24 .…”
Section: Discussionsupporting
confidence: 87%
“…Such results indicate that not all child oral health-related behaviors are related to parents/guardians SOC, corroborating the findings of Qiu et al 19 (2013) and differing from those found in national studies [14][15][16] . Comparable results were also found in studies with adults 20 and adolescents 21 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…18,19 Second, oral problems, such as dental caries, are potential stressors, and given that SOC is related to the ability of caregivers to solve them, this construct can influence how caregivers perceive their children's oral needs. 20,21 A recent systematic review has concluded that there is scientific evidence that SOC exerts an influence on OHRQoL. 22 However, it has also been demonstrated that few studies, mainly cohort studies, have investigated the relationship between the caregivers' SOC and its impact on the OHRQoL of young children.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers, particularly mothers, play a crucial role in their children's oral health, not only because of individual and biological factors but also because their socio-economical determinants are related to infants' caries risk [22]. The experience of ECC and dental pain in children is related to parents' educational and economic level: the most disadvantaged mothers have offspring with the highest prevalence of dental caries in both dentitions [23].…”
mentioning
confidence: 99%